Management of dermatophytosis with a novel itraconazole formulation: a research survey - Haldar, Susmit (International Journal of Research in Dermatology, 2020)
Background: Dermatophytic infections are the most prevalent fungal infections, which affect majority of the global population. Indian climate, especially the hot and humid conditions contribute majorly to dermatophytosis. Itraconazole is an orally active triazole antifungal drug, which has demonstrated a broad spectrum of activity and a favourable pharmacokinetic profile. Itraconazole at an appropriate dosage and duration schedule has been reported to be an effective antifungal drug and has achieved optimal results. Methods: The present survey aimed at evaluating the efficacy of the novel itraconazole formulation, I-Tyza 100 [itraconazole 100 mg (Abbott health care pvt ltd)] with multi-particulate in solid dispersion (MPSD) technology in patients with tinea infections. The data collection was based on the proportion of patients presenting in the clinics for tinea infections, the choice and duration of therapy, real life efficacy of the drug, and for understanding the overall antifungal therapy in dermatomycosis. Results: The responses obtained from 177 doctors were evaluated, and statistical analyses were carried out. The results suggested that clinical presentation of patients with tinea infections per week ranged between 30% and 60%. For the management of tinea infections, oral itraconazole was preferred by maximum doctors, followed by terbinafine, griseofulvin and fluconazole. Also, majority of the doctors (83%) opined that MPSD technology could improve therapeutic efficacy of the novel itraconazole formulation. Conclusions: The survey findings indicated that the novel itraconazole formulation is a preferred oral antifungal therapy for the management of tinea infections.